HAK REPRODUKSI DALAM BATASAN HUKUM: ANALISIS NORMATIF TERHADAP LARANGAN SUROGASI DI INDONESIA - Farah Fahira Putri; Yovita Arie Mangesti (Yayasan Nusantara Hasana Berdikari, 2025)
This study provides a conceptual innovation in policies addressing surrogacy practices in Indonesia from the perspective of the right to reproductive health care. This study applies a normative method using both a statutory and conceptual approach. Referring to Health Law 17/2023, Government Regulation 28/2024, and Ministerial Regulation 2/2025, this study finds that the national legal system has prohibited aspects of surrogacy practices to prevent harm to its values. Instead, the law states that a household is a reciprocal legal obligation, the equivalence and wisdom of which are inherent in their duties as husband and wife and cannot be disturbed by any third party. Therefore, the law prohibits and criminalizes any form of cooperation that would damage the image, meaning, and purpose of married life between the parties concerned. Conversely, the law protects women from bodily exploitation and the commodification of the womb, and ensures that the development of medical technology remains within the law and human values. The study concludes that the prohibition of surrogacy is not a medical obstacle, but rather an active right of the state to judges to ensure that health law serves as a basis for justice.